Effects of Increasing Fat Levels in Diets Containing 40% Distillers Dried Grains with Solubles on Growth Performance and Carcass Characteristics in Commercial Finishing Pigs - Jenna J. Bromm; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 2,160 pigs (PIC 337 × 1050; initially 82.26 lb) were used in two groups to evaluate the effects of increasing added fat levels in diets containing high levels of DDGS on growth performance and carcass characteristics of finishing pigs. Pens of pigs were blocked by initial BW and randomly assigned to 1 of 4 dietary treatments with 27 pigs per pen and 20 pens per treatment. Three of the four dietary treatments included increasing percentages of added fat (choice white grease; 0, 1, or 3%). The final treatment was fed the control diet without added fat until pigs were approximately 220 lb and then pigs were fed a diet containing 3% added fat until market. Overall, increasing fat from 0 to 3% of the diet led to a decrease (linear,P= 0.006) in ADFI and improvement (linear,P= 0.007) in overall F/G. Pigs fed diets containing 3% added fat had the lowest ADFI and improved F/G compared to pigs fed diets containing 0% fat, with the other treatments intermediate. There was a tendency for a linear increase (P= 0.055) in HCW with increasing fat, where pigs fed the 3% fat diet for the entire trial tended to have the heaviest HCW. Increasing fat increased (linear,P<0.001) feed cost per pig and feed cost per lb of gain. This ultimately reduced (linear,P<0.001) income over feed cost (IOFC) for both the low and high cost scenarios. Pigs fed diets containing 3% added fat had the lowest IOFC compared to pigs fed diets containing no added fat, with the other two treatments intermediate. In conclusion, increasing levels of added fat in the diet from 0 to 3% throughout the duration of the study reduced ADFI with no effect on ADG, resulting in an improvement in F/G. When pigs fed the diet without added fat were transitioned to a diet containing 3% added fat on d 69, they had similar F/G compared to pigs fed 3% added fat during the remainder of the trial. Under both low and high cost scenarios tested, the improvement in feed efficiency does not justify the extra diet cost from increasing added fat in the diet for the entire trial or in late finishing.
Keywords: carcass characteristics; economical return; fat level; finishing pigs; growth performance